Methods for Streamlining Intervention Fidelity Checklists: An Example from the Chronic Disease Self-Management Program - Ahn, SangNam; Smith, Matthew Lee; Altpeter, Mary; Belza, Basia; Post, Lindsey; Ory, Marcia G. (Frontiers in Public Health, 2015)
*